Negative Ion Beam Focusing in a Plasma Sputter-type Negative Ion Source - Yambot, Miguel; Mendenilla, Alexander; Valmoria, Nico; Ramos, Henry; Garcia, Alipio (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The ion beam produced from a plasma sputter-type negative ion source with Zr target was analyzed, and the negative ion beam current was increased by focusing with an electrostatic Einzel lens. An Ar-N2 plasma at 7.0x 10-3 Torr (20%N2) with discharge current voltage=-20 V and discharge current=1.0 A was produced for sputter formation of negative ions in the ion source. The Zr target immersed in the plasma was biased at -200 V. The ion beam was analyzed with a retarding potential electrostatic energy analyzer. Lens potentials of 20.0 V for the outer electrodes and -80.3 V for the inner electrode resulted in the highest negative ion beam current, increasing the ion current to 0.5 nA (from 0.28 nA when not using the lens), and reduced the beam spot size to 25 mm (from 35 mm for the unfocused beam).
Keywords: negative ion source; electrostatic einzel lens